The object relationship theory in bioenergetic analysis in the light of Kernberg’s conception - Fellmann, Thomas (Bioenergetic Analysis, 2025)
It is shown how the students further developed Lowen’s bioenergetic concepts, which, in the light of object relations theories, can be traced back to Winnicott in particular. However, to date, Kernberg’s ideas are largely absent from the bioenergetic literature. Lowen’s model of pathogenesis, with the idea of pleasure orientation as the main motivation for human action and physical defense as a means of repressing anxiety in connection with suppressed impulses, is contrasted with Kernberg’s idea of the dynamic unconscious. Based on a modified drive model, he understands affects as the basic motivation for human action. These organize themselves according to their valence into antagonistic poles of aggression and libido. He understands the defense function as a means of splitting painful relationship dyads from conscious self-experience. The three-elements of the object relations are also understood in their physically tangible dimensions, with a focus on the energetic aspect. Daniel Stern’s concept of RIGS supports this connection, which Kernberg does not conceptualize in this way. Krause’s modular affect theory provides guidance for working with the element of affect. The grounding phenomenon known in bioenergetics is reinterpreted by means of Kernberg’s psychodynamic understanding and the possibilities of the interventions derived from it are explained on the basis of a clinical example.